Preformulation studies on the fruit extract of Averrhoa bilimbi L. (Oxalidaceae) and evaluation of its antifertility activity - Betterley, Jesipaz Michelle P.
The fruit juice extract of Averrhoa bilimbi L. was subjected to a preformulation study. This was carried out by conducting stability testing at various temperatures and compatibility testing with several excipients such as tablet binders, disintegrants, glidants, and lubricants. Phytochemical screening was done to determine the presence of chemical constituents in the fruit.